War: Its Morality and Significance - Narveson, Jan (Conatus - Journal of Philosophy, 2023)
This brief paper is a general treatment of war – its morality and its political and social effects. Accordingly, we discuss primarily those armed interactions between nations, or, in “civil” wars, those aimed at securing the reins of government. These must, we contend, be inherently immoral on one side – the one which “starts” the war in question – and inherently moral on the other, who after all are defending their lives against the first. To say this requires a moral theory, which we briefly develop. It proceeds on Hobbesian-contractarian lines: if mankind occupies a “state of nature,” then we will all be worse off than if we join with each other in adopting the restrictions of morality – fundamentally, and primarily, of nonviolence, of living at peace with each other. This raises a question about the very rationality of war, to be sure. And yet, war we have, in considerable and unfortunate abundance. How can this be? Some tentative answers are suggested.